Short-Term Evaluation in Growing Rats of Diet Containing Bacillus thuringiensis Cry1Ia12 Entomotoxin: Nutritional Responses and Some Safety Aspects. (16th August 2010) - Guimarães, Luciane Mourão; Farias, Davi Felipe; Muchagata, Relinda Campos Carvalho; de Magalhães, Mariana Quezado; Campello, Cláudio Cabral; Rocha, Thales Lima; Vasconcelos, Ilka Maria; Carvalho, Ana Fontenele Urano; Mulinari, Fernanda; Grossi-de-Sa, Maria Fátima
Abstract : The Cry1Ia12 entomotoxin from a Brazilian Bacillus thuringiensis strain is currently being expressed in cotton cultivars to confer resistance to insect-pests. The present study aimed to assess the effects of a diet containing Cry1Ia12 protein on growing rats. A test diet containing egg white and Cry1Ia12 (0.1% of total protein) as a protein source was offered to rats for ten days. In addition, an acute toxicity bioassay was performed in rats with a single oral dose of the entomotoxin (12 mg/animal). No adverse effects were observed in the animals receiving the test diet when compared to those receiving a control diet (egg white). The analysed parameters included relative dry weight of internal organs, duodenum histology, blood biochemistry, and nutritional parameters. The results of the acute toxicity test showed no mortality or behaviour alteration. Thus, Cry1Ia12 toxin at the tested concentration does not cause deleterious effects on growing rats when incorporated in the diet for 10 days.